An economic analysis of tolvaptan compared with fluid restriction among hospitalized patients with hyponatremia. Issue 3 (27th May 2017) - Ramamohan, Varun; Mladsi, Deirdre; Ronquest, Naoko; Kamat, Siddhesh; Boklage, Susan
ABSTRACT: Objective : The vasopressin-receptor antagonist tolvaptan is used for the treatment of hyponatremia (HN) in hospitalized patients with congestive heart failure (CHF) or syndrome of inappropriate antidiuretic hormone secretion (SIADH). The objective of this economic modeling study was to assess the potential cost and health outcomes associated with tolvaptan in comparison with fluid restriction (FR). Methods : A decision-analytic model was developed to estimate potential cost and health outcomes associated with tolvaptan compared with FR among hospitalized CHF and SIADH patients with severe HN (serum sodium [SS] levels < 125 mEq/L). The model, which was populated with data from the published literature, assumes that response to treatment influences hospital length of stay, probability of an intensive care unit (ICU) admission, and probability of a 30-day all-cause hospital readmission. One-way and probabilistic sensitivity analyses (PSAs) assessed the influence of parameter uncertainty on model results. Results : Model results suggest that, among hospitalized CHF patients with severe HN, the use of tolvaptan compared with FR may lead to reductions of 7.2% and 4.6% in ICU admissions and 30-day readmissions, respectively. Compared with FR, tolvaptan may result in total cost-savings of 156 per hospitalized CHF patient. Among hospitalized SIADH patients with severe HN, the model suggested reductions of 14.6% and 5.1% in ICU admissions and 30-day readmissions, respectively. Compared with FR, tolvaptan may result in total cost-savings of 135 per hospitalized SIADH patient. PSAs found that the probabilities of net cost-savings from the use of tolvaptan compared with FR were 64% and 59% among patients with severe HN with CHF and SIADH, respectively. Conclusions : Decision-analytic modeling based on published data for hospitalized CHF and SIADH patients with severe HN, indicates that tolvaptan compared with FR has the potential to improve health outcomes and produce cost-savings that more than offset the cost of tolvaptan.